In the name of justice : women and law in society - Mukhopadhyay, Swapna (Manohar, 1998)
Papers presented at the National Seminar on 'Women and Law', at New Delhi, 3-4 December 1994, jointly organized by the Institute of Social Sciences Trust, New Delhi and United Nations Economic and Social Commission for Asia and the Pacific.